Orthodox Mission among Indigenous Small Peoples: History and Modernity - Serapion (Mitko) (Вестник Свято-Филаретовского института, 2017)
The mission of the Russian Orthodox Church among the indigenous small peoples of the North, Siberia and the Far East was historically carried out in the context of solving the accompanying logistics, information, linguistic, apologetic, cultural and anthropological problems. The current situation is characterised by a significant transformation of these problems and the need to rethink the mission’s goals and objectives. The evangelisation of peoples living within the pastoral responsibility of the Moscow Patriarchate has always been an important task and a determining factor in the formation of its canonical territory. The present-day canonical area of the Russian Orthodox Church is constituted primarily by missionaries whose activities always preceded the creation of dioceses.